Efektivitas Media Smart Board untuk Meningkatkan Kemampuan Penjumalahan dengan Teknik Menyimpan pada Anak Disabilitas Intelektual - Apriani, Sonia; Mahdi, Arisul; Iswari, Mega; Kusumastuti, Grahita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to determine the effectiveness of smart board media in improving addition skills using the storage technique for children with intellectual disabilities. This research uses a quantitative approach with an experimental research method in the form of Single Subject Research (SSR) A-B design. The subject of this study is a child with intellectual disabilities with the initials RR who attends SLB Negeri 1 Linggo Sari Baganti in the 9th grade. The technique for data collection is in the form of tests. The data analysis technique is conducted using visual graphic analysis. The analysis results were carried out over 18 meetings. The data obtained at each condition, namely the baseline phase (A1), were conducted over 3 meetings with percentage scores of 0%, 0%, 0%. In the intervention condition (B), a total of 15 meetings were held with percentage scores of 20%, 20%, 30%, 50%, 50%, 60%, 70%, 70%, 80%, 80%, 80%, 90%, 90%, 90%, 90%. Based on the research results that have been conducted, it proves that the smart board media is effective in enhancing the addition skills using the saving technique in children with intellectual disabilities at SLB Negeri 1 Linggo Sari Baganti